Promoting assessment for learning: Students’ perceptions of informal assessment in the English classroom - Sri Rejeki (International Journal in Applied Linguistics of Parahikma, 2020)
This study aims at investigating students' perceptions of informal assessment conducted by the teacher. This assessment provides a solution regarding the fact that many Indonesian students feel frustrated due to the use of formal assessment. The participants of this study were 22 graduate students majoring in English Education in one of the universities in Indonesia. The design of this study was qualitative. This study used observation and a questionnaire to collect the general data and an interview to investigate students' more in-depth understanding. The finding revealed two aspects: the types of informal assessment by the lecturers and the benefits of using informal assessments in the learning activities. The types of assessment the lecturers were linguistic and nonlinguistic aspects, presentation, observation, giving compliment, group discussion, question and answer, interview, and portfolio. Furthermore, several benefits of this assessment viewed from students’ perspective were they more focused on the process instead of the judgment, they got useful feedback based on the learning problems faced by the students, they could solve their learning problems using the feedback given, and it made them more motivated in participating the classroom activities, they felt less stressful while doing this assessment, they got more knowledge and more in-depth understanding about the material, they got reflections which is very crucial in altering their learning progress, and it improved their participation in the classroom activities.